Improved Learning Outcomes of Natural Science Lessons Through Problem Based Learning (PBL) Model Assisted By Power Point Media - Nurziammah, Desi (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve the learning outcomes of students in science mupel in grade V elementary schools with a power point-assisted Problem Based Learning (PBL) learning model. The research conducted is Class Action Research (PTK) as many as two cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementation, observation and reflection. Each meeting is conducted pre test and post test to know the development of students. In cycle I students who completed after carrying out the post test by 82%. In cycle II students completed after carrying out post tests by 93%. These results show that the Problem Based Learning (PBL) learning model can improve the learning outcomes of students, especially the Grade V science teacher at SDN 2 Pabuwaran.